Organic acid components in the cultured medium of some phosphate solubilizing microorganism strains - Phuong Chi, Nguyen Thi; Ha, Pham Thanh; Quynh Mai, Nguyen Thi (Academia Journal of Biology, 2014)
Organic acid components in the cultured medium of some phosphate solubilizing microorganism strains